ADP-Ribosylation of NLRP3 by Mycoplasma pneumoniae CARDS Toxin Regulates Inflammasome Activity - Santanu Bose (American Society for Microbiology, 2014)
ABSTRACT The inflammasome is a major regulator of inflammation through its activation of procaspase-1, which cleaves prointerleukin-1β (pro-IL-1β) into its mature form. IL-1β is a critical proinflammatory cytokine that dictates the severity of inflammation associated with a wide spectrum of inflammatory diseases. NLRP3 is a key component of the inflammasome complex, and multiple signals and stimuli trigger formation of the NLRP3 inflammasome complex. In the current study, we uncovered a yet unknown mechanism of NLRP3 inflammasome activation by a pathogen-derived factor. We show that the unique bacterial ADP-ribosylating and vacuolating toxin produced by Mycoplasma pneumoniae and designated community-acquired respiratory distress syndrome (CARDS) toxin activates the NLRP3 inflammasome by colocalizing with the NLRP3 inflammasome and catalyzing the ADP-ribosylation of NLRP3. Mutant full-length CARDS toxin lacking ADP-ribosyltransferase (ADPRT) activity and truncated CARDS toxins unable to bind to macrophages and be internalized failed to activate the NLRP3 inflammasome. These studies demonstrate that CARDS toxin-mediated ADP-ribosylation constitutes an important posttranslational modification of NLRP3, that ADPRT activity of CARDS toxin is essential for NLRP3 inflammasome activation, and that posttranslational ADPRT-mediated modification of the inflammasome is a newly discovered mechanism for inflammasome activation with subsequent release of IL-1β and associated pathologies. IMPORTANCE Inflammation is a fundamental innate immune response to environmental factors, including infections. The inflammasome represents a multiprotein complex that regulates inflammation via its ability to activate specific proinflammatory cytokines, resulting in an effective host protective response. However, excessive release of proinflammatory cytokines can occur following infection that skews the host response to “hyperinflammation” with exaggerated tissue damage. Mycoplasma pneumoniae, a common bacterial airway pathogen, possesses a unique protein toxin with ADP-ribosyltransferase and vacuolating properties capable of reproducing the robust inflammation and cytopathology associated with mycoplasma infection. Here, we show that the toxin uniquely activates the NLRP3 inflammasome by colocalizing with and ADP-ribosylating NLRP3, possibly leading to “hyperinflammation” and thus uncovering a novel target for therapeutic intervention.